Heteromultimeric P2X(1/2) Receptors Show a Novel Sensitivity to Extracellular pH - BROWN, SEAN G. (J Pharmacol Exp Ther, 2002)
Rat P2X(1) and P2X(2) subunits were coexpressed in defolliculated Xenopus oocytes and the resultant P2X receptors studied under voltage-clamp conditions. Extracellular ATP elicited biphasic inward currents, involving an initial rapidly inactivating (P2X(1)-like) component and a later slowly inactivating (P2X(2)-like) component. The maximum amplitude of P2X(1)-like ATP responses was increased in some cells by lowering extracellular pH (from 7.5 to 6.5), whereas P2X(2)-like responses and those of homomeric rP2X(1) and rP2X(2) receptors were not changed by this treatment. Concentration-response (C/R) curves for ATP for pH-enhanced P2X(1)-like responses were biphasic, and clearly distinct from monophasic ATP C/R curves for homomeric rP2X(1) and rP2X(2) receptors. Under acidic (pH 5.5 and 6.5) and alkaline (pH 8.5) conditions, ATP C/R curves for P2X(1)-like responses showed increases in agonist potency and efficacy, compared with data at pH 7.5, but the same was not true of homomeric rP2X(1) and rP2X(2) receptors. ATP C/R curves for P2X(2)-like responses overlay C/R curves for homomeric rP2X(2) receptors, and determinations of agonist potency and efficacy were identical for P2X(2)-like and P2X(2) responses at all pH levels tested. Our results show that P2X(1)-like responses possessed the kinetics of homomeric P2X(1) receptors but an acid sensitivity different from homomeric P2X(1) and P2X(2) receptors. In contrast, the P2X(2)-like responses exactly matched the profile expected of homomeric P2X(2) receptors. Thus, coexpression of P2X(1) and P2X(2) subunits yielded a mixed population of homomeric and heteromeric P2X receptors, with a subpopulation of novel pH-sensitive P2X receptors showing identifiably unique properties that indicated the formation of heteromeric P2X(1/2) ion channels.